Assessment the Genotoxic Potential of Fluoxetine and Amitriptyline at Maximum Therapeutic Doses for Four-Week Treatment in Experimental Male Rats - Al-Obaidi, Imad A.; N. Al-Shawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2021)
Abstract At any moment, the continuous usage of medications can accompanied by DNA damage and the accumulation of such damages can cause serious consequences. Antidepressants are long-term used drugs and the incidence of their genotoxic impacts cannot be excluded. Therefore, this work was designed to investigate the possible genotoxic effects of the commonly used antidepressants (fluoxetine and amitriptyline) in adult male rats.Detection of DNA damage in individual cells was assessed by comet and micronucleus assays in three different cell populations i.e. liver, testis and bone marrow tissues of 24 swiss albino adult male rats. The animals were randomly allocated into three groups of 8 rats each: Group I - rats orally-administered distilled water via gavage tube for four weeks as a negative control. Group II - rats orally-treated with fluoxetine hydrochloride solution (7.2mg/kg/day) via gavage tube for four weeks. Group III - rats orally-treated with amitriptyline hydrochloride solution (27mg/kg/day) via gavage tube for four weeks.The results showed that both drugs (Group II and Group III) induced the same extent of DNA damage, as evidenced by a significantly higher DNA fragmentation in liver and testis tissues with increased frequencies of micronuclei formation in bone marrow tissues as compared with the negative control (Group I).These findings indicates that both Fluoxetine and Amitriptyline have genotoxic potentials and can induce the same extent of cytogenetic damage in rats. Special precautions and medical supervision should be taken in consideration with their uses.